Biomass carbon dots as well as preparation method and application thereof

By using aniline-modified flavonol compounds to prepare biomass carbon dots, the problems of limited UV absorption capacity and low visible light transmittance in the prior art are solved, and the broad-spectrum UV absorption and high visible light transmittance in the UVA and UVB ranges are achieved, which improves its application potential in the agricultural field.

CN119774590APending Publication Date: 2025-04-08GUANGDONG POLYTECHNIC NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411833336.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing biomass carbon dots have only limited UV absorption capacity in the UVA or UVB range and have low visible light transmittance, which limits its application.

Method used

Aniline-modified flavonol compounds are used as precursors to prepare biomass carbon dots through solvothermal reactions. Combined with the ultrasonic dissolution step, carbon dots with good ultraviolet absorption capacity in the UVA and UVB ranges are obtained, and while maintaining high visible light transmittance, their ability to resist ultraviolet high temperature aging is improved.

Benefits of technology

The broad-spectrum ultraviolet absorption capacity of biomass carbon dots in the UVA and UVB ranges is achieved, while maintaining high visible light transmittance, significantly improving its application potential in the agricultural field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186078180000081
    Figure BDA0005186078180000081
  • Figure HDA0005186078190000011
    Figure HDA0005186078190000011
  • Figure HDA0005186078190000012
    Figure HDA0005186078190000012
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, and discloses a biomass carbon dot as well as a preparation method and application thereof. The biomass carbon dots are prepared from the following raw materials: aniline and flavonol compounds. According to the biomass carbon dot provided by the invention, flavonol compounds derived from biomass such as luteolin and peanut shells are taken as raw materials, nitrogen doping is carried out through aniline, and the biomass carbon dot has relatively good ultraviolet absorption capacity in UVA and UVB ranges and also has excellent visible light permeability and high-temperature ultraviolet aging resistance; the preparation method of the biomass carbon dots is simple in steps, raw materials are easy to obtain, and one-step synthesis can be achieved through a solvothermal method; the biomass carbon dots are doped on the basis of a common polyurethane film, the ultraviolet absorption capacity of the film in UVA and UVB ranges is remarkably improved, meanwhile, the visible light transmittance of the film is not affected, the weather resistance of the film is good, the film is suitable for the agricultural field, and normal photosynthesis can be guaranteed while ultraviolet damage to crops is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a biomass carbon dot and a preparation method and application thereof. Background Art

[0002] The diameter of carbon dots is in the range of 1-10nm, and they are a new type of nanomaterial. Their small size and large specific surface area give them many unique physical and chemical properties, one of which is ultraviolet absorption. The absorption of carbon dots in UVA (wavelength 320-400nm) and UVB (wavelength 275-320nm) comes from the n-π* transition caused by CO / CN in the surface functional groups and the π-π* transition of the conjugated C=C bond.

[0003] There are many precursors and preparation methods for carbon dots. Among them, using biomass as a precursor to prepare carbon dots has the advantages of low cost, low toxicity, and good biocompatibility. However, most of the existing biomass carbon dots only have ultraviolet absorption capabilities within the UVA or UVB range, and have low visible light transmittance, which greatly limits the application of biomass carbon dots. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a biomass carbon dot; the second purpose of the present invention is to provide a method for preparing the biomass carbon dot; the third purpose of the present invention is to provide a polyurethane film; the fourth purpose of the present invention is to provide the application of the polyurethane film.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A first aspect of the present invention provides a biomass carbon dot, comprising the following preparation raw materials: aniline and flavonol compounds.

[0007] The biomass carbon dots provided by the present invention are flavonol compounds modified by aniline.

[0008] In some embodiments of the present invention, the solid-to-liquid ratio of the flavonol compound to aniline is 1 g:(1-12) mL.

[0009] In some specific embodiments of the present invention, the solid-to-liquid ratio of the flavonol compound to aniline is 1 g:(2-5) mL.

[0010] In some embodiments of the present invention, the flavonol compound is selected from at least one of luteolin and kaempferol.

[0011] In the present invention, flavonol compounds in biomass are used as precursors for preparing carbon dots. Flavonols refer to compounds containing 2-phenyl-3-hydroxy (or oxygen-substituted) benzoγ-pyrone (2-phenyl-3-hydroxychromone), which are the largest type of flavonoid compounds. Luteolin can be separated from the branches, leaves and stems of oleander. In addition, peanut shells are also rich in luteolin, which is one of the waste products of peanuts. The development and utilization of luteolin in peanut shells can improve the comprehensive utilization value of peanuts. Kaempferol is widely distributed in a variety of vegetables and fruits such as leeks, onions, mung beans, pumpkins, potatoes, tomatoes, strawberries, and traditional Chinese herbal medicines such as forsythia, rosemary, acacia, ginkgo leaves, mimosa, cinnamon, etc., and has a wide range of sources.

[0012] In some embodiments of the present invention, the raw material for preparing the biomass carbon dots further includes alcohol.

[0013] In some embodiments of the present invention, the alcohol is selected from at least one of methanol and ethanol.

[0014] In some embodiments of the present invention, the biomass carbon dots are brown solid.

[0015] The second aspect of the present invention provides a method for preparing the biomass carbon dots according to the first aspect of the present invention, comprising the following steps:

[0016] The flavonol compounds, aniline and alcohol are mixed to carry out a solvothermal reaction to obtain the biomass carbon dots.

[0017] In some embodiments of the present invention, the solid-liquid ratio of the flavonol compound to the alcohol is 1 g: (40-100) mL.

[0018] In some specific embodiments of the present invention, the solid-liquid ratio of the flavonol compound to the alcohol is 1 g: (80-100) mL.

[0019] In some embodiments of the present invention, the temperature of the solvothermal reaction is 170-210°C.

[0020] In some specific embodiments of the present invention, the temperature of the solvothermal reaction is 190-210°C.

[0021] In some embodiments of the present invention, the solvent thermal reaction time is 6-12 hours.

[0022] In some specific embodiments of the present invention, the solvent thermal reaction time is 6-8h.

[0023] In some embodiments of the present invention, after the flavonol compound, aniline and alcohol are mixed, a step of ultrasonic dissolution is further included.

[0024] In some embodiments of the present invention, the ultrasonic dissolution time is 5-10 min.

[0025] In some embodiments of the present invention, the solvothermal reaction is carried out in a stainless steel autoclave equipped with a polytetrafluoroethylene (PTFE) liner.

[0026] In some embodiments of the present invention, after the solvothermal reaction is completed, the steps of filtering and drying are further included.

[0027] In some embodiments of the present invention, the pore size of the filter is less than or equal to 0.22 μm.

[0028] In some embodiments of the present invention, the drying temperature is 80-100°C.

[0029] The third aspect of the present invention provides a polyurethane film, comprising the biomass carbon dots described in the first aspect of the present invention.

[0030] In some embodiments of the present invention, the raw materials for preparing the polyurethane film include biomass carbon dots and waterborne polyurethane (PU).

[0031] In some embodiments of the present invention, in the polyurethane film, the content of the biomass carbon dots is 0.02-0.15 wt %.

[0032] In some specific embodiments of the present invention, in the polyurethane film, the content of the biomass carbon dots is 0.02-0.1 wt %.

[0033] In some embodiments of the present invention, the polyurethane film is prepared by a method comprising the following steps:

[0034] The biomass carbon dots are mixed with waterborne polyurethane and dried to obtain the polyurethane film.

[0035] The fourth aspect of the present invention provides the use of the polyurethane film described in the third aspect of the present invention in the agricultural field.

[0036] In some embodiments of the present invention, the application includes using the polyurethane film as an agricultural greenhouse covering film.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1) The biomass carbon dots provided by the present invention use flavonol compounds derived from biomass such as osmanthus and peanut shells as raw materials, and are nitrogen-doped by aniline modification. The biomass carbon dots have good ultraviolet absorption capacity in the UVA and UVB ranges, and also have excellent visible light transmittance and resistance to ultraviolet high temperature aging;

[0039] 2) The preparation method of biomass carbon dots provided by the present invention has simple steps, readily available raw materials, mild reaction conditions, and can be synthesized in one step by a solvothermal method, which is suitable for popularization and use;

[0040] 3) The polyurethane film provided by the present invention is doped with biomass carbon dots on the basis of ordinary polyurethane film, which significantly improves the ultraviolet absorption capacity of the film in the UVA and UVB ranges, while not affecting the visible light transmittance of the film;

[0041] 4) The polyurethane film provided by the present invention has good weather resistance and is suitable for the agricultural field. It can reduce the ultraviolet damage to crops and ensure the normal photosynthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a physical picture of the carbon dot LA-CDs-1 in Example 1;

[0043] Figure 2 This is a physical picture of the carbon dots L-CDs in Comparative Example 1;

[0044] Figure 3 This is the ultraviolet absorption-transmission spectrum of the carbon dot LA-CDs-1 in Example 1;

[0045] Figure 4 The ultraviolet absorption-transmission spectra comparison diagram of the carbon dots in Example 1 and Comparative Example 1;

[0046] Figure 5 The figure is a comparison of the ultraviolet absorption spectra of the carbon dots in Example 1 and Comparative Examples 1-5;

[0047] Figure 6 This is a comparison chart of the ultraviolet absorption performance of carbon dots at different aniline doping levels;

[0048] Figure 7 is the anti-aging ultraviolet absorption spectrum of the carbon dots in Example 1;

[0049] Figure 8 It is the visible light transmission spectra of the polyurethane films in Application Examples 1-5 and Comparative Example 1. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0051] Example 1

[0052] In this example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass, and the steps are as follows:

[0053] S1. Pour 0.25 g of luteolin and 0.5 mL of aniline into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0054] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-1.

[0055] Example 2

[0056] In this example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass, and the steps are as follows:

[0057] S1. Pour 0.5 g of luteolin and 1 mL of aniline into 40 mL of ethanol, dissolve under ultrasound for 8 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 210 °C for 8 h to perform a solvothermal reaction;

[0058] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-2.

[0059] Example 3

[0060] In this example, a biomass carbon dot was prepared using kaempferol, a flavonol compound derived from biomass, and the steps are as follows:

[0061] S1. Pour 0.25 g of kaempferol and 0.5 mL of aniline into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0062] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-3.

[0063] Comparative Example 1

[0064] In this comparative example, luteolin, a flavonol compound derived from biomass, was used to prepare a biomass carbon dot. The only difference from Example 1 was that aniline was not doped. The steps were as follows:

[0065] S1. Pour 0.25 g of luteolin into 20 mL of ethanol and dissolve it by ultrasonic for 5 min. Seal the mixture in a stainless steel autoclave equipped with a PTFE liner and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction.

[0066] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots L-CDs.

[0067] Comparative Example 2

[0068] In this comparative example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass. The difference from Example 1 is that o-phenylenediamine was used for doping and modification. The steps are as follows:

[0069] S1. Pour 0.25 g of luteolin and 0.5 mL of o-phenylenediamine into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0070] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-4.

[0071] Comparative Example 3

[0072] In this comparative example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass. The difference from Example 1 is that m-phenylenediamine was used for doping and modification. The steps are as follows:

[0073] S1. Pour 0.25 g of luteolin and 0.5 mL of m-phenylenediamine into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0074] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-5.

[0075] Comparative Example 4

[0076] In this comparative example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass. The difference from Example 1 is that p-phenylenediamine was used for doping and modification. The steps are as follows:

[0077] S1. Pour 0.25 g of luteolin and 0.5 mL of p-phenylenediamine into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0078] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-6.

[0079] Comparative Example 5

[0080] In this comparative example, a biomass carbon dot was prepared using luteolin, a flavonol compound derived from biomass. The difference from Example 1 is that ethylenediamine was used for doping and modification. The steps are as follows:

[0081] S1. Pour 0.25 g of luteolin and 0.5 mL of ethylenediamine into 20 mL of ethanol, dissolve under ultrasound for 5 min, seal the mixture in a stainless steel autoclave equipped with a PTFE liner, and heat it in an oven at 200 °C for 6 h to perform a solvothermal reaction;

[0082] S2. After the reaction is completed, wait for the reaction solution to cool to room temperature, filter it with an organic filter with a pore size of 0.22 μm, transfer the filtered solution to a beaker, and place it in a 90°C oven for drying to obtain carbon dots LA-CDs-7.

[0083] Application Example 1

[0084] In this application example, the carbon dots LA-CDs-1 prepared in Example 1 are used as raw materials to prepare a polyurethane film, and the steps are as follows:

[0085] Add 3 mL of aqueous polyurethane into a beaker, then add 83 μL of carbon dot LA-CDs-1 solution, stir the mixed solution until it is uniform, pour it into a culture dish with a diameter of 5 cm, and place it in an oven at 60°C until the film falls off to obtain a polyurethane film LA-CDs-1@PU-1, which is stored in a dry container. The content of LA-CDs-1 in LA-CDs-1@PU-1 is 0.02 wt%.

[0086] Application Example 2

[0087] In this application example, the carbon dots LA-CDs-1 prepared in Example 1 are used as raw materials to prepare a polyurethane film, and the steps are as follows:

[0088] Add 3 mL of aqueous polyurethane into a beaker, then add 167 μL of carbon dot LA-CDs-1 solution, stir the mixed solution until it is uniform, pour it into a culture dish with a diameter of 5 cm, and place it in an oven at 60°C to dry until the film falls off to obtain a polyurethane film LA-CDs-1@PU-2, which is stored in a dry container. The content of LA-CDs-1 in LA-CDs-1@PU-2 is 0.04 wt%.

[0089] Application Example 3

[0090] In this application example, the carbon dots LA-CDs-1 prepared in Example 1 are used as raw materials to prepare a polyurethane film, and the steps are as follows:

[0091] Add 3 mL of aqueous polyurethane into a beaker, then add 251 μL of carbon dot LA-CDs-1 solution, stir the mixed solution until it is uniform, pour it into a culture dish with a diameter of 5 cm, and place it in an oven at 60°C to dry until the film falls off to obtain a polyurethane film LA-CDs-1@PU-3, which is stored in a dry container. The content of LA-CDs-1 in LA-CDs-1@PU-3 is 0.06 wt%.

[0092] Application Example 4

[0093] In this application example, the carbon dots LA-CDs-1 prepared in Example 1 are used as raw materials to prepare a polyurethane film, and the steps are as follows:

[0094] Add 3 mL of aqueous polyurethane into a beaker, then add 335 μL of carbon dot LA-CDs-1 solution, stir the mixed solution until it is uniform, pour it into a culture dish with a diameter of 5 cm, and place it in an oven at 60°C to dry until the film falls off to obtain a polyurethane film LA-CDs-1@PU-4, which is stored in a dry container. The content of LA-CDs-1 in LA-CDs-1@PU-4 is 0.08 wt%.

[0095] Application Example 5

[0096] In this application example, the carbon dots LA-CDs-1 prepared in Example 1 are used as raw materials to prepare a polyurethane film, and the steps are as follows:

[0097] Add 3 mL of aqueous polyurethane into a beaker, then add 420 μL of carbon dot LA-CDs-1 solution, stir the mixed solution until it is uniform, pour it into a culture dish with a diameter of 5 cm, and place it in an oven at 60°C to dry until the film falls off to obtain a polyurethane film LA-CDs-1@PU-5, which is stored in a dry container. The content of LA-CDs-1 in LA-CDs-1@PU-5 is 0.1 wt%.

[0098] Application Comparative Example 1

[0099] This application example prepares a polyurethane film, and the steps are as follows:

[0100] 3 mL of waterborne polyurethane was poured into a Petri dish with a diameter of 5 cm, and placed in an oven at 60° C. for drying until the film fell off, thereby obtaining a polyurethane film PU-1, which was stored in a dry container.

[0101] Characterization and performance testing

[0102] 1. Appearance Characterization

[0103] Figure 1 is a physical picture of the carbon dot LA-CDs-1 in Example 1, Figure 1 It can be seen that the luteolin biomass carbon dots doped with aniline are brown solids.

[0104] Figure 2 The physical picture of the carbon dots L-CDs in Comparative Example 1 is shown in FIG. Figure 2 It can be seen that the luteolin biomass carbon dots without aniline doping modification are yellow solid.

[0105] 2. Carbon dot UV absorption-transmission performance test

[0106] 1) Take the LA-CDs-1 carbon dot solution before drying in Example 1 and perform ultraviolet absorption and visible light transmission tests:

[0107] Figure 3 is the ultraviolet absorption-transmission spectrum of the carbon dots LA-CDs-1 in Example 1, Figure 3 It can be seen that the carbon dots LA-CDs-1 prepared in Example 1 produced absorption peaks at 269nm, 286nm and 351nm, covering the absorption of UVA (wavelength 320-400nm), UVB (wavelength 275-320nm) and UVC (wavelength 200-275nm), basically achieving the effect of full ultraviolet absorption. In addition, the carbon dots LA-CDs-1 have a high visible light transmittance at a wavelength of 400-800nm, indicating that the aniline-doped modified luteolin biomass carbon dots provided by the present invention have both a wide range of ultraviolet absorption properties and can ensure that their visible light transmittance is not affected.

[0108] 2) Comparison of ultraviolet absorption and visible light transmittance performance of the carbon dot solutions before drying in Example 1 and Comparative Example 1:

[0109] Figure 4 is a comparison chart of the ultraviolet absorption-transmission spectra of the carbon dots in Example 1 and Comparative Example 1, Figure 4It can be seen that the carbon dots in Comparative Example 1 have not been modified by aniline doping, and have ultraviolet absorption ability in the UVA and UVB ranges, and have a high visible light transmittance. After aniline doping modification is performed on the basis of Comparative Example 1, Example 1 has a significantly improved ultraviolet absorption ability of the carbon dots in the UVB range, the ratio of the absorption peak intensities in the UVA and UVB ranges is close to 1:1, and the visible light transmittance is not affected.

[0110] 3) Comparison of ultraviolet absorption and visible light transmittance performance of the carbon dot solutions before drying in Example 1 and Comparative Examples 1-5:

[0111] Figure 5 is a comparison chart of the ultraviolet absorption spectra of the carbon dots in Example 1 and Comparative Examples 1-5, Figure 5 It can be seen that compared with no nitrogen doping, doping with aniline, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine and ethylenediamine can improve the ultraviolet absorption performance of carbon dots in the UVB range to a certain extent. Among them, the effect of doping with aniline and ethylenediamine is the most significant. However, after ethylenediamine doping, the ultraviolet absorption performance of carbon dots in the UVA range drops sharply, and it has a great obstacle to the transmission of visible light. Therefore, doping with aniline alone can make the carbon dots have better ultraviolet absorption ability in both UVA and UVB ranges, as well as better visible light transmittance.

[0112] 3. Influence of aniline doping amount

[0113] On the basis of Example 1, the amounts of other raw materials were kept unchanged, and only the amount of aniline added was changed. Figure 6 The comparison chart of the ultraviolet absorption performance of carbon dots under different aniline doping amounts is shown in Figure 2. Figure 6 It can be seen that with the increase of the aniline doping amount, the absorption capacity of the carbon dots in the UVB range is slightly improved, and the absorption capacity in the UVA range is slightly decreased. However, when the amount of aniline is increased to 6 times the amount in Example 1, the change in the ultraviolet absorption performance of the carbon dots is not significant, indicating that when the present invention is doped with aniline, excellent performance can be obtained with a very small amount.

[0114] 4. Experiment on the aging resistance of carbon dots

[0115] The carbon dots LA-CDs-1 in Example 1 were placed in a UV weathering aging test box (60°C) for aging experiments, and the UV absorption properties of the carbon dots were tested before the start of the experiment (0 day), 1 day, 7 days, 14 days, 1 month, 2 months, 3 months, 4 months and 5 months after the start of the experiment. Figure 7 is the anti-aging ultraviolet absorption spectrum of the carbon dots in Example 1, Figure 7It can be seen that in the first four months of the aging experiment, the anti-ultraviolet ability of the carbon dot LA-CDs-1 was not affected by ultraviolet rays and high temperature, and it still maintained high-efficiency ultraviolet absorption ability. After five months of ultraviolet irradiation and high temperature, the ultraviolet absorption performance of LA-CDs-1 decreased, but it still maintained the ability to absorb within the UVA and UVB ranges.

[0116] 5. Polyurethane film UV absorption-transmission performance test

[0117] The visible light transmittance of the polyurethane film in Example 1-5 and Comparative Example 1 was tested. Figure 8 The visible light transmission spectra of the polyurethane films in Application Examples 1-5 and Comparative Example 1 are shown in FIG. Figure 8 It can be seen that compared with the pure polyurethane film in Comparative Example 1, the polyurethane films doped with carbon dots in Example 1 prepared in Examples 1-5 also have better visible light transmittance.

[0118] Table 1 shows the absorption efficiency and average transmittance data of the polyurethane films in Application Examples 1-5 and Application Comparative Example 1:

[0119] Table 1 Absorption efficiency and average transmittance data of polyurethane films in application examples 1-5 and comparative example 1

[0120]

[0121] As shown in Table 1, with the increase of the doping amount of carbon dots in Example 1, the ultraviolet absorption performance of the polyurethane film gradually improves. When the doping amount is only 0.02wt%, the ultraviolet absorption rate can reach 92.2%, and the average visible light transmittance can reach 95%. With the increase of the doping amount of carbon dots, the average visible light transmittance gradually decreases, but it can also be above 86%, indicating that the polyurethane film provided by the present invention, after being doped with a very small amount of carbon dots, can achieve a significant improvement in ultraviolet absorption performance while maintaining the visible light transmittance of the pure polyurethane film. The polyurethane film provided by the present invention can be applied to the agricultural field, such as as an agricultural greenhouse covering material, by absorbing ultraviolet rays through the film, reducing the harm of ultraviolet rays to crops, thereby reducing leaf burns and other damage caused by ultraviolet rays; while allowing sufficient visible light to pass through, it helps plants to photosynthesize and promotes plant growth.

[0122] The biomass carbon dots provided by the present invention have readily available raw materials and a simple preparation method. They have ultraviolet absorption capabilities within the ranges of UVA and UVB, and have a high visible light transmittance. The carbon dots have excellent resistance to ultraviolet and high-temperature aging. The polyurethane film containing the biomass carbon dots has significantly improved ultraviolet absorption performance and is substantially unaffected in visible light transmittance, and is suitable for the agricultural field. The film has good weather resistance, can reduce the harm of ultraviolet rays to crops, and ensure the normal conduct of photosynthesis.

Claims

1. A biomass carbon dot, characterized in that: The invention comprises the following preparation raw materials: aniline and flavonol compounds.

2. The biomass carbon dots according to claim 1, characterized in that: The solid-to-liquid ratio of the flavonol compound to aniline is 1 g:(1-12) mL.

3. The biomass carbon dots according to claim 1, characterized in that: The flavonol compound is selected from at least one of luteolin and kaempferol.

4. The biomass carbon dots according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the biomass carbon dots also include alcohol.

5. The method for preparing biomass carbon dots according to claim 4, characterized in that: The following steps are involved: The flavonol compounds, aniline and alcohol are mixed to carry out a solvothermal reaction to obtain the biomass carbon dots.

6. The preparation method according to claim 5, characterized in that: The solid-to-liquid ratio of the flavonol compound to the alcohol is 1g: (40-100)mL.

7. The preparation method according to claim 5, characterized in that: The temperature of the solvent thermal reaction is 170-210°C; And / or, the solvent thermal reaction time is 6-12h.

8. A polyurethane film, characterized in that: Comprising the biomass carbon dots according to any one of claims 1 to 4.

9. The polyurethane film according to claim 9, characterized in that: In the polyurethane film, the content of the biomass carbon dots is 0.02-0.15 wt %.

10. Use of the polyurethane film according to claim 8 or 9 in the agricultural field.

Citation Information

Cited By

  • Lysosome-oriented luteolin carbon dots as well as preparation method and application thereof

    CN121975519A